2010
DOI: 10.1007/s12015-010-9214-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Umbilical Cord Lining Cell with CD227 Positivity and Unique Pattern of P63 Expression and Function

Abstract: Umbilical cord tissue is gaining attention as a novel source of multipotent stem cells because it is easily obtainable, ethically acceptable and the cells are immunologically naïve. In this study, we have isolated and characterized a new cell type expressing MUCIN1 (CD227) from human umbilical cord lining which we termed MUCIN-expressing Cord Lining Epithelial Cell (CLEC-muc). We found that CLEC-muc is highly proliferative and had significant clonogenic ability. These cells express embryonic stem cell markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 45 publications
3
31
1
Order By: Relevance
“…Furthermore, other than the two discussed above, MSCs from both origins do not express embryonic SC markers, such as TERT, Rex-1, Sox-2, FGF-4, although we recently found that CL-MSCs expressed Rex-1 and Sox-2 [22]. In our first report, we could not detect both Rex-1 and Sox-2 mRNA [19].…”
Section: Comparison Of Cell Surface and Intra-cellular Markerscontrasting
confidence: 52%
“…Furthermore, other than the two discussed above, MSCs from both origins do not express embryonic SC markers, such as TERT, Rex-1, Sox-2, FGF-4, although we recently found that CL-MSCs expressed Rex-1 and Sox-2 [22]. In our first report, we could not detect both Rex-1 and Sox-2 mRNA [19].…”
Section: Comparison Of Cell Surface and Intra-cellular Markerscontrasting
confidence: 52%
“…8,25,26 Similar to human UCECs, SUCECs were highly proliferative and expressed embryonic stem cell and pluripotency markers including SSEA-1, SSEA-4, TRA-1-60, TRA-1-81, and Oct-4 and showed in vitro differentiation potential. 25,26 The expression of these factors indicated that these cells possess many of the properties of embryonic cells. Consistent with the expression of stem cells markers, SUCECs possessed self-renewal and differentiation potential.…”
Section: Discussionmentioning
confidence: 98%
“…Cells from the umbilical cord lining (UCL) have also been isolated by means of explant method after separation and dissection of the UCL membrane [65,66]. Different cell populations have been obtained depending on the culture medium ( Table 4).…”
Section: Mscs From the Umbilical Cord Liningmentioning
confidence: 99%
“…Interestingly, these cells also expressed CD14, that is a component of the innate immune system and they are present on macrophages, neutrophil granulocytes, and dendritic cells [67]. On the other hand, Reza et al, [66] have grown UCL cells in PTTe-1 medium containing components that preferentially support epithelial cell growth. As a result, a cell population possessing properties of both epithelial cells and embryonic stem cells has been obtained.…”
Section: Mscs From the Umbilical Cord Liningmentioning
confidence: 99%